The level of blood plasma mitochondrial DNA upon acute myocardium damage in experiment - Sudakov, N.P.; Popkova, T.P.; Novikova, M.A.; Katyshev, A.I.; Nikiforov, S.B.; Pushkarev, B.G.; Goldberg, O.A.; Klimenkov, I.B.; Lepekhova, S.A.; Ezhikeeva, S.D.; Ten, M.N.; Osipov, V.G.; et al. (Вiopolymers and Cell, 2012)
The aim of the present investigation is to study the level of plasma mtDNA as a potential marker of cardiomyocyte damage in 2 and 4 h after subcutaneous injection of adrenaline and during the formed morphological alterations of the myocardium (3 days). Methods. Real time PCR. Male Wistar rats were used as the experimental animals. Results. It was shown that during the increase in the activity of cytolysis biomarkers, at the first hours after adrenaline injection, no reliable increase is observed in the level of free circulating blood mtDNA. A tendency of 2.5-fold increase in this parameter was established at the third day after adrenaline injection during the development of acute inflammatory process in the myocardium. On the whole, further researches are needed on the dynamics of mtDNA level upon acute damage of the myocardium in experimental and clinical investigations for unbiased estimation of the prospects of using the parameter in laboratory diagnostics.
Keywords: mitochondrial DNA, cardiovascular diseases, adrenaline myocarditis, cytolysis biomarkers. Цель. Изучить уровень мтДНК плазмы крови как возможного маркера повреждений кардиомиоцитов через 2 и 4 ч после подкожной инъекции адреналина и на фоне сформированных морфологических изменений миокарда (3-и сут). Методы. Полимеразная цепная реакция в реальном времени. В экспериментах использовали самцов крыс линии Вистар. Результаты. Показано, что наряду с увеличением активности биомаркеров цитолиза в первые часы после введения адреналина значимого повышения уровня свободно циркулирующей мтДНК крови не происходит. Установлена тенденция к 2,5-кратному возрастанию данного показателя на 3-и сут после инъекции адреналина на фоне развития острого воспалительного процесса в миокарде. Выводы. В целом для объективной оценки перспектив этого показателя в лабораторной диагностике инфаркта миокарда необходимо дальнейшее изучение динамики уровня мтДНК при острых повреждениях миокарда в экспериментальных и клинических исследованиях.
Ключевые слова: митохондриальная ДНК, сердечно-сосудистые заболевания, адреналиновый миокардит, биомаркеры цитолиза. Мета. Вивчити рівень мтДНК плазми крові як можливого маркера пошкоджень кардіоміоцитиів через 2 і 4 год після підшкірної ін’єкції адреналіну та на фоні сформованих морфологічних змін міокарда (3-тя доба). Методи. Полімеразна ланцюгова реакція у реальному часі. В експериментах використано самців щурів лінії Вістар. Результати. Показано, що поряд із збільшенням активності біомаркерів цитолізу в перші години після введення адреналіну суттєвого підвищення рівня вільно циркулюючої мтДНК крові не відбувається. Встановлено тенденцію до 2,5-разового зростання даного показника на 3-тю добу після ін’кції адреналіну на фоні розвитку гострого запального процесу в міокарді. Висновки. У цілому для об’єктивної оцінки перспектив цього показника у лабораторній діагностиці інфаркта міокарда необхідно подальше вивчення динаміки рівня мтДНК при гострих ураженнях міокарда в експериментальних і клінічних дослідженнях.
Ключові слова: мітохондріальна ДНК, серцево-судинні захворювання, адреналіновий міокардит, біомаркери цитолізу.